Shaping a Desired Future for Australian Business Education : Learning from a Successful Scoping and Development Project. - Boyle, Patrick (Australian Learning and Teaching Council (ALTC), 2008)
The ALTC funded Scoping Study in Business Education (Project) was highly successful. It achieved its important objectives and a number of other valuable outcomes for the future of university business education in Australia. It has enhanced the strength of business education networks and stakeholder groups by enabling real collaboration and learning within and across groups. As a result, a wider and more sophisticated network now exists and is well placed to facilitate evolution of learning and teaching in business faculties and programs. In addition, lessons from the management of the Project provide valuable guidance for people who are planning, engaged in or leading educational development initiatives. This case study identifies and briefly describes the main factors responsible for the Project's success. To provide a suitable context, it also provides a synopsis of the Project in terms of its goals, activities and results. [Author abstract]